2001
DOI: 10.1086/318201
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Missense Mutations in the C-Terminal Region of Factor H in Atypical Hemolytic Uremic Syndrome

Abstract: Hemolytic-uremic syndrome (HUS) is a microvasculature disorder leading to microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure. Most cases of HUS are associated with epidemics of diarrhea caused by verocytotoxin-producing bacteria, but atypical cases of HUS not associated with diarrhea (aHUS) also occur. Early studies describing the association of aHUS with deficiencies of factor H suggested a role for this complement regulator in aHUS. Molecular evidence of factor H involvement in aHUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
205
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 270 publications
(224 citation statements)
references
References 35 publications
(25 reference statements)
16
205
0
Order By: Relevance
“…In sporadic forms, the mutation was either inherited from a healthy parent or, more rarely-only four cases reported-ensued de novo in the proband (100,102). The mutation frequency is up to 40% in familial forms, whereas only 13 to 17% of sporadic forms had HF1 mutations (100,119).…”
Section: Genetic Studiesmentioning
confidence: 99%
“…In sporadic forms, the mutation was either inherited from a healthy parent or, more rarely-only four cases reported-ensued de novo in the proband (100,102). The mutation frequency is up to 40% in familial forms, whereas only 13 to 17% of sporadic forms had HF1 mutations (100,119).…”
Section: Genetic Studiesmentioning
confidence: 99%
“…Among the reported cases, approximately 50% had mutations of the complement regulatory proteins factor H (CFH) (7)(8)(9)(10)(11)(12), membrane cofactor protein (13)(14)(15), or factor I (16)(17)(18); mutations occurred less frequently in factor B (19), C3 (20), and thrombomodulin (21).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data have shown that FH binds to cell surfaces via its C-terminal recognition domain which is contained in CCPs 19-20 (Pangburn, 2002;Manuelian et al, 2003;Jokiranta el al., 2005;Józsi et al, 2006;Ferreira et al, 2006). This has medical relevance since FH mutations associated with atypical hemolytic uremic syndrome (aHUS) cluster in the C-terminus of the protein (Caprioli et al, 2001;Pérez-Caballero et al, 2001;Richards et al, 2001). Recombinant FH proteins which have aHUSassociated amino acid exchanges in the C-terminal CCPs 19 and 20 and patient-derived mutant FH proteins show defective binding to heparin, glycosaminoglycans, C3b/C3d and to endothelial cells (Hellwage et al, 2002;Sánchez-Corral et al, 2002Manuelian et al, 2003;Jokiranta et al, 2005;Józsi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%